A Prospective Cohort Study of the Association Between Body Mass Index and Incident Bacterial Vaginosis. Issue 1 (January 2019) - Lokken, Erica M.; Richardson, Barbra A.; Kinuthia, John; Mwinyikai, Khamis; Abdalla, Amina; Jaoko, Walter; Mandaliya, Kishorchandra; Shafi, Juma; Scott McClelland, R.
Background: Some studies suggest that higher body mass index is associated with increased susceptibility to bacterial vaginosis (BV), but results are conflicting. Methods: Female sex workers aged 16 to 45 years and participating in an open, prospective cohort study in Mombasa, Kenya between 2000 and 2014 were included in this analysis. Up to 2 years of follow-up were included per woman. Body mass index (BMI) was categorized as underweight (⩽18.5), normal (18.5–24.9), overweight (25–29.9), and obese (≥30). Bacterial vaginosis was assessed using Nugent scores. Generalized estimating equations were used to estimate relative risks of the association between BMI and BV. Results: At baseline, 32.1% (n = 625) of 1946 women had BV. Half of women were overweight (31.1%, n = 606) or obese (20.1%, n = 391). Participants contributed 14, 319 follow-up visits. Adjusting for age, compared to women with normal BMI, overweight (adjusted relative risk, 0.91; 95% confidence interval, 0.81–1.02) and obese (adjusted relative risk, 0.82; 95% confidence interval, 0.71–0.94) women were at lower risk for BV (joint P = 0.03). Conclusions: Obese women had a nearly 20% lower risk of BV compared with women with normal BMI. Potential mechanisms for this effect, including possible effects of diet, obesity-associated changes in the gut microbiome, and systemic estrogen levels, should be explored. Abstract : A prospective cohort study of female sex workers in Mombasa, Kenya found that obese women had a nearly 20% lower risk of incident bacterial vaginosis compared with normal weight women.